Comparative electrochemical oxidation of methyl orange azo dye using Ti/Ir-Pb, Ti/Ir-Sn, Ti/Ru-Pb, Ti/Pt-Pd and Ti/RuO2 anodes. (1st August 2017) - Isarain-Chávez, Eloy; Baró, Maria Dolors; Rossinyol, Emma; Morales-Ortiz, Ulises; Sort, Jordi; Brillas, Enric; Pellicer, Eva
Graphical abstract: Highlights: Synthesis of dimensionally stable anodes by the dipping method using metallic chlorides Anodic oxidation of methyl orange with Ir-Pb, Ir-Sn, Ru-Pb, Pt-Pd and RuO2 deposited onto Ti 96%-98% decolorization achieved with Ti/Ir-Pb, Ti/Ir-Sn and Ti/Ru-Pb anodes Increasing mineralization power as Ti/RuO2 < Ti/Pt-Pd < Ti/Ru-Pb < Ti/Ir-Sn < Ti/Ir-Pb Detection of stable byproducts and short carboxylic acids by GC-MS and HPLC Abstract: The relative oxidation power of dimensionally stable anodes, namely Ti/Ir-Pb, Ti/Ir-Sn, Ti/Ru-Pb, Ti/Pt-Pd and Ti/RuO2, has been determined from the anodic oxidation (AO) treatment of 2 dm 3 of methyl orange azo dye solutions in 0.050 mol dm −3 Na2 SO4 of pH 7.0 at constant current density. The anodes were synthesized by the dip-coating method using the corresponding metallic chlorides in isopropanol/water and their morphology, surface roughness, crystallographic structure and composition were analyzed. A mixture of IrO2, Pb2 O3 and Pb3 O4 were the components in the outperforming Ti/Ir-Pb anode. The effect of current density, Na2 SO4 concentration, and cathode nature on the decolorization of azo dye solutions by AO with Ti/RuO2 was examined. Under favorable conditions, 96%-98% color removal was achieved using Ti/Ir-Pb, Ti/Ir-Sn and Ti/Ru-Pb, with lower decolorization for Ti/Pt-Pd and Ti/RuO2 anodes. In all cases, a pseudo-first-order decolorization process was found. The oxidation ability of anodes rose in the order Ti/RuO2 < Ti/Pt-Pd < Ti/Ru-Pb < Ti/Ir-Sn < Ti/Ir-Pb, achieving 76.0% mineralization for the latter electrode. The mixture of active and non-active materials then gave rise to anodes with higher oxidation power than those made solely of active materials, due to the enhancement of the oxidation action of hydroxyl radicals formed in the non-active oxide. The superiority of Ir over Ru in the mixed metal oxides was related to the greater adsorption of organics on its surface, thereby favoring their oxidation. Ammonium and sulfate ions were released as pre-eminent ions. Stable byproducts and final short-linear aliphatic carboxylic acids were identified by gas chromatography-mass spectrometry and ion-exclusion high-performance liquid chromatography. Based on these compounds, a reaction sequence for methyl orange mineralization is proposed.